Theoretical Study of Direct Carbon Dioxide Conversion to Formic Acid on Transition Metal-doped Subnanometer Palladium Clusters - Adhitya Gandaryus Saputro; Arifin Luthfi Maulana; Fine Dwinita Aprilyanti; Hermawan Kresno Dipojono (Journal of Engineering and Technological Sciences, 2021)
We studied the direct conversion of CO2 to HCOOH through hydrogenation reaction without the presence of base additives on the transition metal-doped subnanometer palladium (Pd7) cluster (PdxM: M = Cu, Ni, Rh) by using a combination of density functional theory and microkinetic calculations. It was shown that the CO2 hydrogenation on Pd7 and Pd6M clusters are more selective towards the formate pathway to produce HCOOH than the reverse water gas shift pathway to produce CO. Inclusion of Ni and Rh doping in the subnanometer Pd7 cluster could successfully enhance the turnover frequency (TOF) for CO2 hydrogenation to formic acid at low temperature. The order of TOF for formic acid formation is as follows: Pd6Ni > Pd6Rh > Pd7 > Pd6Cu. This order can be explained by the trend of the activation energy of CO2 hydrogenation to formate (HCOO*). The Pd6Ni cluster has the highest TOF value because it has the lowest activation energy for the formate formation reaction. The Pd6Ni system also has a superior TOF profile for HCOOH formation compared to several metal surfaces in low and high-temperature regions. This finding suggests that the subnanometer PdxNi cluster is a promising catalyst candidate for direct CO2 hydrogenation to formic acid.